Finding Evolutionary Processes Hidden in Cryptic Species. (March 2018) - Struck, Torsten H.; Feder, Jeffrey L.; Bendiksby, Mika; Birkeland, Siri; Cerca, José; Gusarov, Vladimir I.; Kistenich, Sonja; Larsson, Karl-Henrik; Liow, Lee Hsiang; Nowak, Michael D.; Stedje, Brita; Bachmann, Lutz; et al.
Abstract : Cryptic species could represent a substantial fraction of biodiversity. However, inconsistent definitions and taxonomic treatment of cryptic species prevent informed estimates of their contribution to biodiversity and impede our understanding of their evolutionary and ecological significance. We propose a conceptual framework that recognizes cryptic species based on their low levels of phenotypic (morphological) disparity relative to their degree of genetic differentiation and divergence times as compared with non-cryptic species. We discuss how application of a more rigorous definition of cryptic species in taxonomic practice will lead to more accurate estimates of their prevalence in nature, better understanding of their distribution patterns on the tree of life, and increased abilities to resolve the processes underlying their evolution. Highlights: Current definitions of cryptic species are inconsistent and can lead to biased estimates of species diversity. Cryptic species are often implied to represent taxa displaying low phenotypic disparity in relation to divergence time, but this relationship is usually not formally quantified. Here we propose a quantitative framework, which provides a formal characterization of the intuitive concept of cryptic species. The proposed framework facilitates understanding of evolutionary processes leading to and resulting from cryptic species and provides a basis for estimates and modeling of occurrences of cryptic species across taxa and environments. The framework fosters a shift from pattern- to process-driven research concerning cryptic species.